A mixed‐methods systematic review of nurse‐led interventions for people with multimorbidity. (5th September 2022) - McParland, Chris; Johnston, Bridget; Cooper, Mark
Abstract: Aims: To identify types of nurse‐led interventions for multimorbidity and which outcomes are positively affected by them. Design: Mixed‐methods systematic review following the Joanna Briggs Institute (JBI) methods for convergent‐integrated reviews. PROSPERO ID: CRD42020197956. Data Sources: Cochrane CENTRAL, CINAHL, Embase and MEDLINE were searched in October 2020. Grey literature sources included OpenGrey, the Journal of Multimorbidity and Comorbidity and reference mining. Review Methods: English‐language reports of nurse‐led interventions for people with multimorbidity were included based on author consensus. Two reviewers performed independent quality appraisal using JBI tools. Data were extracted and synthesized using a pre‐existing taxonomy of interventions and core outcome set. Results: Twenty studies were included, with a median summary quality score of 77.5%. Interventions were mostly case‐management or transitional care interventions, with nurses in advanced practice, support to self‐manage conditions, and an emphasis on continuity of care featuring frequently. Patient‐centred outcomes such as quality of healthcare and health‐related quality of life were mostly improved, with mixed effects on healthcare utilization, costs, mortality and other outcomes. Conclusion: Interventions such as case management are agreeable to patients and transitional care interventions may have a small positive impact on healthcare utilization. Interventions include long‐term patient management or short‐term interventions targeted at high‐risk junctures. These interventions feature nurses in advanced practice developing care plans in partnership with patients, to simplify and improve the quality of care both in the long and short‐term. Impact: This is the first mixed‐methods review which includes all types of nurse‐led interventions for multimorbidity and does not focus on specific comorbidities or elderly/frail populations. Using adapted consensus‐developed frameworks for interventions and outcomes, we have identified the common features of interventions and their overall typology. We suggest these interventions are of value to patients and healthcare systems but require localization and granular evaluation of their components to maximize potential benefits.